An Early Evaluation of Italian High Speed Rail Projects - Beria, Paolo; Grimaldi, Raffaele (TeMA - Journal of Land Use, Mobility and Environment, 2011)
Italy has undergone, in the last 15 years, an exceptional public financial effort to build approximately 1,000 km of high speed rail lines. Further extensions are under construction or planned, especially in the most important international relations. This network is widely considered as fundamental to comply the European vision of a continental-wide transport system.The paper analyses the past and the future of such network, where possible from a quantitative point of view. The first part of the article reviews the history of the Alta Velocità scheme, particularly focusing on the issues related to the economic regulation of the investments and the financial troubles at first and then on the present issues related to the regulation of rail services.The analysis of the supply, the time gains, the demand and the costs allows to build a simple but independent evaluation of the past projects from an ex-post perspective, pointing out the successes, but also important critical issues.The second part of the paper analyses the future expansion plans looking at the costs, the existing and expected demand and derives some policy indications and cost reduction strategies capable both to control public expenditure in a period of crisis and not to abandon the idea of a modern and effective rail network.